Q. 125.0( 2 Votes )

# If a + b + c = 0,

Given:

a + b + c = 0

Substituting c = a b in 3ax + by + 2c = 0, we get:

3ax + by – 2a – 2b = 0

a (3x – 2) + b (y – 2) = 0 This line is of the form L1 + λL2 = 0,

which passes through the intersection of the lines L1 and L2, i.e. 3x – 2 = 0 and y – 2 = 0 .

Solving 3 x – 2 = 0 and y – 2 = 0, we get: Hence, the required fixed point is Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation view all courses RELATED QUESTIONS :

If a + b + c = 0,RD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

Find the equationRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics

<span lang="EN-USRD Sharma - Mathematics